Training untuk Mencapai Nilai TOEFL Ideal di Masa Pandemi bagi Mahasiswa Universitas Bumigora - Syamsurrijal Syamsurrijal; Titik Ceriyani Miswaty; M. Zaki Pahrul Hadi (LPPM Universitas Bumigora, 2021)
This community service aims to provide not only knowledge but also readiness to face the TOEFL exam for Bumigora University students. This community service is carried out at Bumigora University for one month. The target community is the campus community, namely students. The method used in this community service is to provide tips and strategies in answering the TOEFL test to UBG students. The cost of this community service activity is fully sourced from the community service implementation team. After the implementation of community service activities in the form of English language training, students have sufficient ability and readiness to take the actual TOEFL test.